Elementary Students Poetry Writing Skills Through Structured Classroom Practice: Keterampilan Menulis Puisi Siswa Sekolah Dasar Melalui Praktik Kelas yang Terstruktur - Rachmadwi Fatmawati; VEVY LIANSARI, MP.d (Academia Open, 2025)
General Background: Poetry writing represents an essential component of language and literary learning in elementary education, supporting students’ literacy, creativity, and emotional expression. Specific Background: Classroom observations indicated that many students experienced difficulties in generating ideas, selecting diction, and organizing poetic lines during writing activities. Knowledge Gap: Previous studies largely discussed general literacy strategies, while limited attention has been given to contextual descriptions of poetry writing instruction and students’ performance in elementary classrooms. Aims: This study aims to describe the learning process, identify supporting and inhibiting factors, and portray students’ poetry writing abilities within a classroom-based implementation. Results: Using a descriptive qualitative design through observation, interviews, and documentation, findings reveal gradual improvement in students’ idea development, vocabulary choice, and confidence in composing poems. Teacher guidance, learning media, and structured activities served as supports, whereas limited time and varied student readiness acted as constraints. Novelty: The study provides a detailed classroom-centered account of poetry instruction combined with analysis of practical enablers and barriers. Implications: The findings suggest the integration of creative tasks, guided practice, and contextual media to foster sustainable literary literacy in elementary education. Keywords: Poetry Writing, Elementary Education, Literacy Learning, Classroom Practice, Creative Expression Key Findings Highlights: Learners produced more organized verses with clearer themes Instructional media and guidance supported active participation Time limits and unequal readiness restricted task completion